2020
DOI: 10.13189/ujer.2020.082581
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Role of the Family in Enhancing the Intellectual Security of Children

Abstract: Family is the fundamental unit in building strong and cohesive societies. Therefore, it is essential to provide the family with a range of mechanisms and skills that help to fulfill its mandated role by immunizing its children from destructive beliefs. Thereby, the family plays a pivotal role in embodying what is known as intellectual security in society, which is a key factor in flourishing society's progress and prosperity. In addition, It plays a decisive role in society cohesion and pursuit to achieve inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…As such, the couple may be likely to neglect their dyadic relationship, and have poor verbal and physical communication, thus leading to emotional divorce. This finding is consistent with those reported in previous studies [ 19 , 59 , 60 ]. Alternatively, it may be easier for couples with no or fewer children to obtain a legal divorce, especially considering custody issues.…”
Section: Discussionsupporting
confidence: 94%
“…As such, the couple may be likely to neglect their dyadic relationship, and have poor verbal and physical communication, thus leading to emotional divorce. This finding is consistent with those reported in previous studies [ 19 , 59 , 60 ]. Alternatively, it may be easier for couples with no or fewer children to obtain a legal divorce, especially considering custody issues.…”
Section: Discussionsupporting
confidence: 94%
“…Studies also indicated that 93% of women with disabilities do not participate in sports and that women make up only a third of athletes with disabilities in international competitions. By giving women with disabilities the opportunity to compete and demonstrate their physical abilities, sports can help reduce gender stereotypes and negative perceptions of women with disabilities (Al-Shahrani and Hammad, 2020;Almateg et al, 2022).…”
Section: Journal Of Disability Research 2024mentioning
confidence: 99%
“…Divorce is a complex process, and although it is not prohibited in Islam, spouses are not encouraged to separate or divorce, especially in societies with strict cultures [11]. The Saudi culture maintains a very cohesive and powerful social process structured around the family unit [28,29]. Divorce is strongly discouraged in Saudi Arabia owing to the prevailing culture and traditions.…”
Section: The Saudi Contextmentioning
confidence: 99%